The offense characteristics of maternal filicides in eSwatini: adding to Resnick’s classification model - Shabangu, Sifiso; Moen, Melanie (Frontiers in Psychology, 2024)
Introduction Maternal filicide, the murder of a child by a mother, is a complex phenomenon. Relatively little is known of filicide on the African continent, especially in eSwatini. This study highlights the complex dynamics at play when these crimes are committed. Methods This retrospective study explored offense characteristics of maternal filicide cases in eSwatini from 2005 to January 2024. Thirty-one cases were identified through court documents and news reports. Content analysis was conducted on these cases. Results The study revealed that socio-cultural factors such as the role of a woman in society and traditional beliefs contributed to these crimes. Poverty and contextual challenges also contributed to the systemic reasons for these murders. Relationship challenges featured prominently. A unique finding in this study was the use of poison by biological mothers in all the filicide-suicide attempts. Discussion We argue for the inclusion of an additional socio-cultural category to Resnick’s classification model. Ultimately, there is a need for further exploration of filicide in eSwatini and other contexts. This would aid in identifying risk factors in pregnant mothers, in young mothers, among couples, and within socio-cultural practices.